Implementation of the BAHA TAM Program for Religious Character Development in Schools: A Qualitative Study - Zubaidi, Ahmad; Maulidiyah, Tausi’iyatul Ilmi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Forming religious character is a crucial aspect of education in instilling moral and spiritual values in students. However, studies on structured school programs in shaping religious character remain limited. SMP Negeri 1 Tongas implements the BAHA TAM program as an innovative effort to systematically develop students' religious character. This study employs a qualitative approach with a field research design. Data were collected through observations, interviews with the principal, teachers, and students, and documentation analysis. The findings reveal that SMP Negeri 1 Tongas applies the BAHA TAM program, which consists of reading, memorization, Tahfidzul Quran, Aqidatul Awwam, and Makhorijul Huruf. Various strategies support the program's effectiveness, including habituation, mentoring, exemplary leadership, collaboration with parents, and adequate facilities and infrastructure. The BAHA TAM program serves as a structured model for religious character formation. The synergy between schools, teachers, and parents is vital in ensuring the program's success, making it a potential reference for other educational institutions. This study contributes to existing literature by providing a detailed analysis of a structured religious character-building program in a public school setting, which is rarely explored in previous studies.